Older people, discrimination and citizenship: What specific insights in light of disability law on the national and international level? - Mercat-Bruns, Marie; Gründler, Tatiana (Aequitas)

(untitled) (Réseau international sur le Processus de production du handicap (RIPPH), 2023)
Our research first delves into the complexity of ageism in law to understand to what extent the existing legal norms are sufficient to encounter the stereotypes linked to old age and the individual as well as systemic discrimination which ensues. According to European and national case law, age is an ambiguous ground of discrimination law and masks the complexity of age discrimination. It seems the scope of the UN Convention on the Rights of People with disabilities overlaps with some difficulties of older people in terms of rights but the CRPD also illustrates how an international convention can be a game changer, creating an impetus to gain insight on the particular characteristics of disability, but not age. The concept of disability discrimination has in turn enriched the way we think of discrimination in a more relational way. In order to prove the inadequacies of the current international legal framework on the human rights of older people, the second part of our study will illustrate how the right to vote exemplifies the challenges of age discrimination in terms of citizenship and full participation of older people in the democratic process, demonstrating the need to adopt a tailored international convention for older individuals.